FINANCING HIGH-TECH PROJECTS THROUGH FOREIGN DIRECT INVESTMENTS - Khoshimov Sabir Murtazaevich; Ganiev Shahiriddin Vohidovich (Western European Studies, 2024)
The article discusses the economic nature and content of financing high-tech projects through foreign direct investment, the role and importance of foreign direct investment in the development of the country's knowledge-intensive industries, existing problems, analytical data, conclusions, proposals and recommendations for solutions
Keywords: investment attractiveness; foreign direct investment; high technology